Quality of Life Hemodialysis Patient and Caregiver: A Correlational Study During Pandemic Covid-19 on Indonesian Sample - Wantonoro Wantonoro; Endang Koni Suryaningsih; Tuan Van Nguyen (Universitas Aisyah Pringsewu, 2022)
The COVID-19 pandemic has caused great panic and anxiety worldwide, including for patients dialysis who reported high mortality and decreased patients quality of life including caregivers. This study aimed to investigate the correlation between the quality of life among patients undergoing hemodialysis and caregiver, especially during COVID-19 in Indonesia. A cross-sectional study design has been adopted. An accidental sampling technique was employed in this study between June and December 2021. Short Form-36 and Hospital Anxiety and Depression Scale were used to measure primary outcomes. Seventy-eight patients receiving hemodialysis and Seventy-eight caregivers were recruited. All of the patients had comorbidities (88.7%) and patients tend to be at a high level of depression and anxiety (53.2%), Middle level of depression and anxiety (30,4%). However, only a few (26.9%) caregivers had comorbidities, and all were without a high level of depression and anxiety. This study shows no correlation between the patients quality of life and the family caregivers quality of life during the COVID-19 pandemic, both from the physical (p 0.43) and mental dimensions (p 0.55). This study concluded that hemodialysis status, being older, a number of comorbidities, and depressing status influence quality of life. Program and specific treatment on depression among end-stage renal disease suggested for future study. Abstrak: Pandemi COVID-19 telah menimbulkan kepanikan dan kecemasan yang luar biasa di seluruh dunia, termasuk bagi pasien cuci darah yang dilaporkan memiliki angka kematian yang tinggi, penurunan kualitas hidup pasien termasuk bagi caregiver. Penelitian ini bertujuan untuk mengetahui hubungan kualitas hidup antara pasien yang menjalani hemodialisis dengan caregiver khususnya selama COVID-19 di Indonesia. Sebuah desain studi cross-sectional telah diadopsi. Teknik pengambilan sampel secara kebetulan digunakan dalam penelitian ini antara bulan Juni dan Desember 2021. Short Form-36 dan Hospital Anxiety and Depression Scale digunakan untuk mengukur hasil primer. Tujuh puluh delapan pasien yang menerima hemodialisis dan Tujuh puluh delapan pengasuh direkrut. Semua pasien memiliki penyakit penyerta (88,7%) dan pasien cenderung berada pada tingkat depresi dan kecemasan tinggi (53,2%), tingkat depresi dan kecemasan sedang (30,4%). Namun, hanya sedikit (26,9%) pengasuh yang memiliki penyakit penyerta, dan semuanya tanpa tingkat depresi dan kecemasan yang tinggi. Penelitian ini menunjukkan tidak ada hubungan antara kualitas hidup pasien dengan kualitas hidup caregiver keluarga selama pandemi COVID-19, baik dari dimensi fisik (p 0,43) maupun mental (p 0,55). Penelitian ini menyimpulkan bahwa status hemodialisis, usia lanjut, jumlah penyakit penyerta, dan status depresi mempengaruhi kualitas hidup. Program dan pengobatan khusus pada depresi di antara penyakit ginjal stadium akhir disarankan untuk studi masa depan.